2021
DOI: 10.3390/ijerph18189538
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Circumstances Associated with Work-Related Suicides from the National Violent Death Reporting System, 2013–2017

Abstract: Workplaces are critical in suicide prevention because work-related factors can be associated with suicide, and because workplaces can be effective suicide prevention sites. Understanding the circumstances associated with work-related suicides can advance worksite prevention efforts. Data from the United States Centers for Disease Control and Prevention, National Violent Death Reporting System from 2013 to 2017 were used to examine characteristics and circumstances associated with work compared with non-work su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The literature concludes that jobs with low control have a higher risk of suicide, which is accentuated by high demand. This explains why low-skilled jobs, with less control over the task, tend to be at higher risk of suicide-related phenomena, both suicidal ideation and attempts ( Peek-Asa et al, 2021 ; Wild et al, 2021 ; Aberg et al, 2022 ; Nishimura et al, 2022 ). It is relevant that when low job control coexists with overqualification of the employee, the risk is accentuated, as it implies a rupture of expectations ( Almroth et al, 2022 ).…”
Section: Work and Suicide Evidence: A Psychosocial Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature concludes that jobs with low control have a higher risk of suicide, which is accentuated by high demand. This explains why low-skilled jobs, with less control over the task, tend to be at higher risk of suicide-related phenomena, both suicidal ideation and attempts ( Peek-Asa et al, 2021 ; Wild et al, 2021 ; Aberg et al, 2022 ; Nishimura et al, 2022 ). It is relevant that when low job control coexists with overqualification of the employee, the risk is accentuated, as it implies a rupture of expectations ( Almroth et al, 2022 ).…”
Section: Work and Suicide Evidence: A Psychosocial Modelmentioning
confidence: 99%
“…A longitudinal analysis of 84,389 suicide cases carried out in the US population concluded that 12.1% of them were directly linked to work-related issues ( Peek-Asa et al, 2021 ). Understanding the phenomenon of suicide as multi-causal ( Abrutyn and Mueller, 2018 ; Mueller et al, 2021 ), we have compiled international literature from the last 4 years that explores the relationship between suicide and precarious working conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature primarily focuses on work-related suicides in the USA, France, Japan, the United Kingdom, Australia, India, China and South Korea, addressing them mainly at the individual and institutional levels (e.g., Amagasa et al, 2005 ; Peek-Asa et al, 2021a ; Jang et al, 2022 ; Waters and Palmer, 2022 ; Sarpong, 2024 ). In addition, studies primarily aim to group work-related suicides according to type or profession or to reveal the triggers of work-related suicides, and these studies attract more attention from the fields of psychiatry, psychology, and organizational behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who attempt work-related suicide, reportedly had financial problems, depression, being evicted, or losing their home. Suicide prevention policies recommend workplaces offer services such as financial planning and psychological support to their employees to prevent work-related suicides ( Peek-Asa et al, 2021a ). Another study conducted in the USA compares death certificates and death investigations and discovers significant inconsistencies between the two documents.…”
Section: Introductionmentioning
confidence: 99%